Identification, quantification and age-related changes of human trabecular meshwork stem cells - Yogapriya Sundaresan (Eye and Vision, 2019)
Abstract Background Loss of cells in the human trabecular meshwork (TM) has been reported with ageing and in glaucoma. This study aims to identify, quantify and determine the age-related changes of human TM stem cells (TMSCs). Methods Isolation of TM cells/ paraffin sectioning was carried out using human corneoscleral rings and whole globes. The TM cells/ sections were immunostained for the stem cell markers ATP-binding cassette protein G2 (ABCG2), nerve growth factor receptor p75 and AnkyrinG (AnkG). Images were acquired using Leica SP8 confocal microscope. The isolated cells were analyzed for two parameters- ABCG2 expression and nucleus to cytoplasmic ratio (N/C ratio). The total number of TM cells and those positive for ABCG2 and p75 in each section were quantified. Spearman rank order correlation was used to determine the association between age and the cell counts. Results The TMSCs were identified based on two parameters- high ABCG2 expression and high N/C ratio > 0.7. These stem cells were also positive for p75 and AnkG. The TMSC content based on the two parameters was 21.0 ± 1.4% in < 30 years age group, 12.6 ± 6.6% in 30–60 years and 4.0 ± 3.5% in > 60 years. The stem cells with high ABCG2 and p75 expression were restricted to the Schwalbe’s line region of the TM. A significant correlation was observed between the reduction in TMSC content and TM cell count during ageing. Conclusion The human TMSCs were identified and quantified based on two parameter analysis. This study established a significant association between age-related reduction in TMSC content and TM cell loss.